Peranan Konten Influencer TikTok dalam Meningkatkan Kunjungan Wisatawan di Yogyakarta - Hatfan Thirafi; Angga Intueri Mahendra Purbakusuma (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The use of social media in Indonesia has been growing rapidly. TikTok has become one of the most frequently used platforms for promotional purposes, particularly in the tourism sector. The high number of TikTok users has given rise to many influencers who hold significant influence over the decisions of their followers as well as others who view their content. In this context, the researcher aims to examine the role of influencer content on TikTok in increasing tourist visits to Yogyakarta. This study employs a descriptive qualitative method with data collected through in-depth interviews involving two influencers (@tentangjogja and @masdolan), the Yogyakarta Tourism Office, and audiences of influencer content. The analysis is carried out using the eight stages of Digital Content Marketing introduced by Kotler, Kartajaya, and Setiawan (2019), starting from goal setting to content marketing improvement. The findings show that the visual content presented by influencers is capable of shaping positive perceptions among customers toward tourist destinations, increasing their interest in visiting, and assisting the Tourism Office in promoting tourism content more extensively on social media. In conclusion, TikTok influencer content plays a crucial role in boosting the number of tourist visits to Yogyakarta, while also serving as an effective communication medium to reach a wider audience.